Effect of Alpha-receptor Blocking Drugs and Disodium Cromoglycate on Histamine Hypersensitivity in Bronchial Asthma. Issue 5702 (18th April 1970) - Kerr, James W.; Govindaraj, M.; Patel, K. R.
Abstract : Twenty patients with extrinsic type bronchial asthma are shown to have a significant fall in vital capacity (V.C.) and forced expiratory volume in 1 second (F.E.V.1 ) after an intravenous infusion of 50μg. of histamine dihydrochloride. In 10 of these subjects the fall in V.C. and F.E.V.1 produced by intravenous histamine is inhibited by the alpha-receptor blocking drugs phentolamine and phenoxybenzamine injected before the histamine test. The inhalation of disodium cromoglycate in 10 subjects is also shown to inhibit the fall in V.C. and F.E.V.1 produced by the intravenous infusion of histamine. It is suggested that bronchial smooth muscle in asthmatic subjects has alpha-adrenergic receptor sites, and that a possible mechanism for the action of disodium cromoglycate is that it stabilizes the cell membrane, thereby altering calcium ion transport.